Kubernetes microservices - Chesterwood, Richard (Manning Publications, 2019)
"Microservices designs require you to change how you build and deploy applications. Instead of creating a tightly-integrated collection of related components, microservices employ a system of single-purpose mini-applications that cooperate as a system. This can get tricky quickly when you're in a distributed cloud-based environment with lots of moving parts. Kubernetes, a component management system developed by Google, provides a configurable layer for deploying, managing, and scaling the parts of a microservices application. Combined with the Docker container system, Kubernetes makes deploying and monitoring microservices on a cloud system like AWS much safer and more stable than using home-brewed processes. In the comprehensive Kubernetes Microservices video course, expert instructor Richard Chesterwood teaches you to deploy and monitor microservice systems on AWS using Kubernetes, Docker, and other industry-standard tools."--Resource description page